A Hybrid, Soft Exoskeleton Glove Equipped with a Telescopic Extra Thumb and Abduction Capabilities - Gerez, Lucas; Dwivedi, Anany; Liarokapis, Minas (Proceedings - IEEE International Conference on Robotics and Automation, 2020)
Over the last years, hand exoskeletons have become a popular and efficient technical solution for assisting people that suffer from neurological and musculoskeletal diseases and enhance the capabilities of healthy individuals. These devices can vary from rigid and complex structures to soft, lightweight, wearable gloves. Despite the significant progress in the field, most existing solutions do not provide the same dexterity as the healthy human hand. In this paper, we focus on the development of a hybrid (tendon-driven and pneumatic), lightweight, affordable, wearable exoskeleton glove equipped with abduction/adduction capabilities and a pneumatic telescopic extra thumb that increases grasp stability. The efficiency of the proposed device is experimentally validated through three different types of experiments: i) abduction/adduction tests, ii) force exertion experiments that capture the maximum forces that can be applied by the proposed device, and iii) grasp quality assessment experiments that focus on the effect of the inflatable thumb on enhancing grasp stability. The hybrid assistive glove considerably improves the grasping capabilities of the user, being able to exert the forces required to assist people in the execution of activities of daily living.
Created from Fastlane, Scopus look-up